Problematyka żydowska w Biblii księdza Jakuba Wujka z 1599 roku - Pietkiewicz, Rajmund (The Biblical Annals, 2019)
The author, on the basis of the study of the commentaries and prefaces to Wujek’s Bible of 1599, depicts the image of the Jews, their language and their customs as it was presented by Jakub Wujek and his contemporaneous fellow Jesuits. The author refers to the sources of the information contained in Wujek’s Bible, evaluates it in the context of the religious situation in the Renaissance Polish-Lithuanian Commonwealth and attempts at establishing the realm and power of the influence it had on readers.